Partai Keadilan Sejahtera dalam Pemberitaan Media - Abdul Rozak (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2016)
This study aims to determine how the Kompas describes and interprets an issue on bribery of beef imports involving an official figure of the Prosperous Justice Party (PKS), Lutfi Hasan Ishaaq. This study used blended methods of quantitative content analysis and framing model of Pan and Kosicki. Quantitative content analysis focused on the use of the printed sources, newpapers points of view, news in general repostage of the PKS and PKS president; while the framing was conducted by investigating the structure of the syntax, script, thematic, and rhetoric of the news. The results obtained by analysis of three conclusions. Firstly, Kompas Newspaper has successfully distinguished itself with a tendency to press earlier era through the use of the printed sources are more diverse, not only rely on official sources of government, and involved parties is a major as part in the news. Secondly, Kompas Newspaper was relatively neutral, objective, and independent. Thirdly, Kompas Newspaper interpreted the bribery case meat imports as a matter of law, not politics.